2022
DOI: 10.53730/ijhs.v6ns5.8922
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with zoonosis and reverse zoonosis of mycobacterium tuberculosis and mycobacterium bovis in Ethiopia

Abstract: Zoonotic TB (M.bovis) is transmitted from animals to people. Mycobacterium tuberculosis is responsible for the transmission of reverse zoonotic tuberculosis from humans to animals. Without sufficient proof, a few recommendations can be made regarding zoonotic and reverse zoonotic transmission. The researchers aimed to review and meta-analysis of risk variables for zoonotic and reverse transmission of bovine tuberculosis. Until May 2022, 13 published publications from Pub-Med, Scopus, Web of Science, and Google… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…In addition, there is a habit of chewing and spitting tobacco to their cattle among Ethiopian farmers. This led to a higher risk of transmission for M. tuberculosis as well as for M. bovis at the human-livestock interface through inhalation of the cough spray from infected animals or transmission of M. tuberculosis from human to cattle as the organism can spread to the animal (Desta et al, 2022).…”
Section: Risk Factors In Humanmentioning
confidence: 99%
“…In addition, there is a habit of chewing and spitting tobacco to their cattle among Ethiopian farmers. This led to a higher risk of transmission for M. tuberculosis as well as for M. bovis at the human-livestock interface through inhalation of the cough spray from infected animals or transmission of M. tuberculosis from human to cattle as the organism can spread to the animal (Desta et al, 2022).…”
Section: Risk Factors In Humanmentioning
confidence: 99%
“…There are many factors which exacerbate the spread of M. bovis to humans and M. tb from human to animals (reverse zoonosis) in LMICs [ 78 ]. In their studies, Desta et al , [ 79 ] and Kouengoua et al , [ 80 ] identified several direct and indirect factors that can influence the spread of tuberculosis between animals and humans. These include demographics like age and gender, along with dietary habits such as consuming unpasteurized milk and meat.…”
Section: Risks Factors For Ztb In Pakistanmentioning
confidence: 99%